Early Learning Impact Analysis State Finance for Students' Concerns about State Budget - Subekan, Achmat; Soderi, Soderi (Budapest International Research and Critics University, 2021)
This study aims to determine the effectiveness of learning state finance for school students and their attitude or concern for the State Revenue and Expenditure Budget (APBN). The theme of state finances, especially the state budget, is not one of the lessons taught to elementary school to high school students. The study was conducted on Junior High School (SMP) students who were participants in the activities of the Ministry of Finance of the State of One State which were organized by the Ministry of Finance online from June 25 to July 8, 2021. Participants were called SANI, an acronym for Satu Negeri. They come from various junior high schools throughout Indonesia. The analysis was conducted using a qualitative method based on the participants' responses to the questionnaire that was sent to them. Questionnaire questions in the form of closed and open questions. Research data were also obtained from several facilitators and observations during the activity. The results showed that the study of state finances (APBN) took place effectively. This effectiveness can be seen from the implementation which can take place well even though it is carried out online. Effectiveness can also be seen from the increase in participants' understanding of state finances (APBN). This effectiveness then has an impact on the attitudes of participants, marked by the emergence of their awareness and concern for the state budget. In the future, this concern will be very meaningful for the sustainability of the APBN both in terms of income and expenditure so that its management can be carried out in a sustainable manner.